Indução floral e vigor da jabuticabeira com aplicação de bioreguladores e irrigação - Kosera Neto, Carlos (2015)
The fruit production sector is one of the major generate income, employment and rural development of national agribusiness. Brazil is one of the main native fruits genetic diversity centers all over the world, which several present domestication potential to commercial use, like jabuticaba fruit tree, that it is specie adapted to several Brazilian edaphoclimatic conditions, which can be used by food, cosmetic and pharmaceutical industry. Among the ifficulties, that still it doesn’t become this potentiality in reality is the long juvenile period, the yield time concentration and the difficult culture, because of vigorous growing. In the implantation of commercial orchards is necessary research to provide culture strategies for reduction of plant vigor, to use in density crop, flowering and yield higher, especially in offseason. Then, it can to use regulators that have antagonism action against growth hormones and it can promote flowering and growth plant control. The products used with successfully in other crops were calcium carbide, ethephon and paclobutrazol (PBZ). Therefore, the aim of this work was evaluate the vegetative and reproductive behavior in the jabuticaba fruit tree (Plinia cauliflora) with regulator application and irrigation. The study was carried out at UTFPR - Câmpus Dois Vizinhos, Paraná State (Brazil), with plants in plastic ots cultivated in open sky conditions. The experiment was random block design with split-plot for almost all over the variables, that levels were of 5 x n (treatment x evaluation time), it being ‘n’ different according with variable evaluated. The plot was each treatment inductor. It was tested four technical flower inductor and the control. The plants control did not had management technique. It was used eight replications of three plants by experimental unit. It was used as inducer treatment, the calcium carbide, ethephon and PBZ applications, irrigation daily (approximately 2 L plant-1 day), and the control. The chemical inducers were applied two times (2014, January and March). The plant height, trunk diameter, shoot and trunk diameter growth percentage, shoots number, shoots length, leaves number, leaves physiological disturb, epidermal detachment on trunk or branches, shoots development stage, leaves area, length and width of leaves, percentage of plants with reproductive structure and its number per tree were evaluated. The results obtained showed that the plant management by daily irrigation did ot provided effect to flowering induction. The ethephon application induced greater growth of shoot, the PBZ showed leaf growth deformities that it did not affected the fruit set and still it induced better yield as well as early flowering. The ethephon treatment showed greater epidermal detachment in jaboticaba fruit tree, but did not have similar effect on the flowering. It possible recommended the use of PBZ to floral induction in jaboticaba fruit tree.